2020
DOI: 10.1055/s-0040-1714035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Fear and Anxiety among Russian Children of Different Ages: The Cross-Sectional Study

Abstract: Abstract Objective Children’s dental fear may lead to an avoidance of seeking dental care or disruptive behavior during treatment. The study was aimed to evaluate the prevalence and scores of dental fear and anxiety (DFA) among Russian children of different ages with an experience of dental treatment. Materials and Methods The cross-sectional study included 371 children aged 2 to 17 years. Study participants were divided into three groups according to their age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…In the literature of recent years, there is considerable variation in the designs of study and target populations, particularly in the scales used for measurement and the age of the children, so that the reported prevalence of dental fear and anxiety in children varies widely, ranging from 7.4% 9 to 93.8%. 10 It can be said that there is currently no fully ideal dental anxiety scale for children in use. Efforts should therefore continue to be directed towards the development and validation of suitable instruments for the detection of dental anxiety in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature of recent years, there is considerable variation in the designs of study and target populations, particularly in the scales used for measurement and the age of the children, so that the reported prevalence of dental fear and anxiety in children varies widely, ranging from 7.4% 9 to 93.8%. 10 It can be said that there is currently no fully ideal dental anxiety scale for children in use. Efforts should therefore continue to be directed towards the development and validation of suitable instruments for the detection of dental anxiety in children.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature of recent years, there is considerable variation in the designs of study and target populations, particularly in the scales used for measurement and the age of the children, so that the reported prevalence of dental fear and anxiety in children varies widely, ranging from 7.4% 9 to 93.8%. 10…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is further supported by the fact that the sample that we examined was older than those in the studies cited above. There is almost total agreement in the literature that younger children tend to admit their fears more freely than older ones, and dental anxiety is expected to decrease as age advances [5,16,17]. The high prevalence (51.7%) of dental fear among Lithuanian children, aged 12-15, was also found in a study conducted by Račienė a decade ago [46].…”
Section: Discussionmentioning
confidence: 78%
“…In general, a recent systematic review with meta-analyses conducted by Grisolia et al (2021) reported that estimates of DFA prevalence in children and adolescents taken from 50 studies worldwide, which used different instruments, ranging from 6% to 75%, had a pooled prevalence of 23.9% (95% CI 20.4-27.3) [5]. The prevalence of DFA varies considerably across countries, with lower estimations in European children and higher estimations in Asian children [16,45]. Therefore, findings from our study in comparison with other studies indicate a relatively high severity of dental fear among the Lithuanian population aged 13-18 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation